KAJIAN PEMBANGUNAN INFRASTRUKTUR PELABUHAN TANJUNG PRIOK TERHADAP PERTUMBUHAN NILAI EKSPOR DI INDONESIA - Maritza, Talita; Aulia, Najma Resti; Mutiara, Dian; Prasaja, Disma (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2025)
Infrastructure development is the main focus for all countries in the world which aims to strengthen the role of each country and also improve its image in terms of international trade. This research aims to analyze the impact of infrastructure development on international trade in Indonesia. We focus on export value as a case study. Using the literature review method through collecting literature review methode, this research examines how infrastructure development at ports and customs facilities is carried out. This research also discusses its supporters over the last few years, customs policies related to post, factors influencing port infrastructure development, development of port infrastructure in recent years, the role of infrastructure development in Indonesia’s exports and imports, modernization of online platform technology at ports. It is hoped that the result of the research will provide a good understanding of the relationship between infrastructure, port and customs development and the progress of international trade in a country. This can also provide guidance for more effective and efficient infrastructure development wisdom, and also help in planning future investments that are sustainable and have a positive impact on the global economy. keyword : Infrastructure, Development, Development Planning. Klasifikasi JEL: O18, O210